 # Interesting Take on Solving an Equation

When asked can Two+ two = five, most of us would give a weird look to the person asking this odd question. Yes, there is no functional equation that proves 2+2= 5. But mathematically, it can be proven correct. Below we’ve shared a couple of expert perspectives to understand the breakdown of the equation.

## Scientific view

Two plus two can equal five if there is a chemical reaction between two compounds with two molecules, each resulting in a single compound containing five molecules.

## Critical view

From the critical perspective, 2 plus 2 can equal five when taken as +1, which someone might forget or erase. Read More

## Mathematical view

When numbers do not add up, several circumstances may arise. It is most common in probability and statistics, where the sum of two numbers does not add up 100%. It mostly occurs because of rounding errors where numbers round to a certain level of precision. Here’s an example to understand the possibilities of 2+2 = 5.

2.49 + 2.48 = 4.97
2.49 rounds up to 2
2.48 rounds up to 2
4.97 rounds up to 5, therefore, 2 + 2 equals to five.

## Statistical view

2 + 2 + 0 = 5

The above statement can be true in statistical analysis. Let’s consider the following example:

2,400,105 people chose green
2,655,555 people chose red
Only 444,340 people chose yellow
Rounding up these into millions,
Two million + two million+ zero million is equal to five million.

2 + 2 = 5 is not valid in arithmetic; however, it is possible in the statistical analysis of these numbers are rounded up precisely.

### Module 1 arithmetic

In module 1 arithmetic, every number is equals to 0, therefore 2 + 2 = 5 can be considered correct. Modulo 1 arithmetic - Every number equals 0, so 2 + 2 = 0 + 0 = 0 = 5Redefine equality: 3 = 4, 4 = 5 but 3 != 5. (non associative equality, otherwise it is just the same as the previous case). Now 2 + 2 = 4 = 5 = 6 = 7 = … But 2 + 2 != 6, because 4 = 5 = 6 does not imply that 4 = 6. This is logically consistent but a very strange kind of reasoning.Define (+) so that x (+) y = x + y + 1. So, 2 (+) 2 = 2 + 2 + 1 = 5. What’s the easiest way out? Just redefine addition.Strange deduction rules or conventions - E.g., use the pattern that you always add 1 to the right-hand side in any equation so that when you say 2 + 2 = 5, you mean the same as what ordinary folk means when they write 2 + 2 = 4. It is not similar to the previous case because, by five on the right-hand side, you mean what most people would call 4. So then, 4 = 5. But5≠45≠4 because four on the right-hand side there would mean what most folk call 3.   Paraconsistent. Just add 2 + 2 = 5 as a new axiom and accept that your axioms' system is inconsistent. You can only use it for very short chains of deduction before you hit a contradiction. Such deduction systems are interesting all the same.  For instance, in real life, we often work with paraconsistent logic systems, where we have a network of inconsistent assumptions. However, we still find it useful to deduce things from them - and from time to time, we hit an inconsistency and revise our beliefs.Numbers that are time-dependent or, for some other reason, are fluid and changing as you go through the equations. So, 2 (+) 2 = 5 because one of the objects you are counting split in two by the time you got to the right-hand side of the equation (if reading left to right) or merged (if you read right to the left) where equations always refer to records of time sequences.

### Proving the Equation by Logic

It is impossible to prove 2+2=5 in maths, but it can be established by LOGIC.

#### LOGIC 1:

(By using floating-point)
Integer’s whole numbers can be positive, negative or zero, but have no decimal places or fractional parts.
Therefore, by using a floating-point, we can rewrite the equation as
2.5+2.5=5

#### LOGIC 2:

2+2=5 Neither is right. Two plus two equals five is not proper, or correct and your left hand is not your right hand.

#### LOGIC 3:

(Multiplying both sides by 0)So 0=0Hence proved

#### Real-life logic

Consider two girls have five apples.However, they want to share them equally.Each one of them will have two apples and share one apple.Since they are having two apples each2+2=4But they have five apples in total2+2=4+1so 2+2=5We can denote the above equation by:2+2=4By using x, let x is shared candy2+2+x=5By putting x=0So 2+2=5.Prove

#### Prove one

We all know, 2+2 = 4=> 2+2
= 4 – 9/2 + 9/2
= √(4 – 9/2)^2 + 9/2
= √(16 – 2*4*9/2 + (9/2)^2) + 9/2
= √(16 – 36 + (9/2)^2) + 9/2
= √(-20 + (9/2)^2) + 9/2
= √(25 – 45 + (9/2)^2) + 9/2
= √(5^2) – 2*5*9/2 + (9/2)^2) + 9/2
= √(5 – 9/2)^2 + 9/2
= 5 – 9/2 + 9/2
= 5……. (proved)

#### Prove two

Let a = ba * a = a * ba^2 = a * ba^2 – b^2 = a * b – b^2(a+b)(a-b) = b(a-b)a+b = b2b = b2 = 11 = 21 + 3 = 2 + 34 = 52+2 =5……. Proved

Is your math homework giving you a hard time? Are you looking for professional assistance with a budget? Don’t panic and get Math assignment help from Allessaywriter.com for extensive academic support. Our experts are real mathematical geniuses and belong from prominent universities in the country. Furthermore, our experts also guarantee:

• Outstanding educational assistance from 1100+ academicians
• Student-friendly deals with additional discounts
• 24*7 live student support
• 100% authentic and plagiarism-free solutions
• Guaranteed on-time delivery of urgent assignments
• Safe and secured payment gateways

### You might also like  ### Best Price

Receive help from top experts in the industry

### Popular Posts

Subscribe to get regular Update!

149
37
4
17
11

order now